The Fracture Process of the Mortar Pump’s Work Surfaces with Abrasive Particles - Kaczynski, Roman; ., Oleksiyvasyliev; Vasyliev, Ievgen (International Journal of Engineering and Technology, 2018)
Using the example of a mortar pump with a flow-through plug the authors of the article offer a mathematical model of the fracture process of the mortar pump’s work surfaces under the action of abrasive sand particles. The influence of different factors, material properties and conditions of wearing on the wear rate are analyzed in this research paper.
Keywords: Mortar pump; abraser wear; wear rate; material performance.